Burning issue: How does copyright affect you as librarians, researchers, teachers? - Nicholson, Denise Rosemary (Library and Information Association of South Africa (LIASA), 2008)
This article defines copyright and provides guidelines to librarians, researchers and teachers on how to apply the Copyright law to reproduction for educational and non-commercial purposes
Keywords: copyright; librarians; researchers; teachers; schools; educational institutions